The Effect of Transformational Leadership Style on Urban Supply Chain Governance in Ahvaz City - s Amanpour; M Safaeepour; S Maleki; H Alizadeh (International Journal of Supply Chain Management, 2018)
Abstract- This paper reports a study of the effect of transformational leadership style on urban supply chain governance in Ahvaz city. We adopted a qualitativequantitative approach to conduct interviews. Two survey questionnaires (for transformational leadership style and urban supply chain governance indicators) were used to collect data from managers and employees working in 8 municipal regions in Ahvaz city, Iran. In order to collect data for this study, our research sample are (N=205) working managers and employees. Our results suggest that transformational leadership style has a significant positive and direct effect on urban supply chain governance. Our findings also show a strong impact between transformational leadership style and participation as urban supply chain governance index. This study offers that extending leadership styles and their applications and influences in urban studies could have great importance, especially urban management and governance. Key word- transformational leadership, urban supply chain governance, participation, effectiveness, Ahvaz